STRATEGI PEMBELAJARAN JARAK JAUH PADA MATA KULIAH MENGGAMBAR TEKNIK : MASALAH, SOLUSI, HAMBATAN, PRAKTIK EFEKTIF - Shofwan ‘Arif (CV. ADIBA AISHA AMIRA, 2025)
The COVID-19 pandemic has had a significant impact on many aspects of human life, especially education. To ensure social distancing, schools were closed, and face-to-face learning was halted until conditions stabilized. Even after the pandemic ended, the remote learning methods used during the pandemic continued to be utilized. This includes vocational education such as technical drawing courses. With students learning from home, teachers faced challenges in preparing for online learning. Effective learning strategies are needed to succeed in online education. This article aims to provide an explanation of successful online learning methods. The data for this scientific article were obtained through a process of identification, evaluation, and synthesis; the researchers used several journals as references and books to support their arguments. The literature review results indicate that 1) Many people are not ready for online learning and face difficulties in achieving learning objectives. 2) Effective online learning strategies are systematic plans created by teachers to address every aspect of online learning. 3) Teachers can use these strategies to achieve effective online learning, such as mastering the use of online media, providing alternative access, enhancing student interaction and participation, and offering support and guidance